Effect of Valerian on Anxiety of Nurses Working in the ICUs: A randomized controlled trial - masoomeh najafzadeh; kourosh amini; soghrat faghihzadeh; hamidreza monsef esfahani (Zanjan University of Medical Sciences and Health Services, 2016)
Background and Objectives: Several studies have shown that nurses working in the ICUs experience high levels of anxiety. Anxiety can not only negatively affect them, but may decrease the quality of care provided by them. The present study aimed to assess the effect of Valerian on anxiety among nurses working in the ICUs of Zanjan teaching hospitals. Materials and Methods: In this clinical trial, nurses working in morning and evening shifts were recruited to the study. A dose of 530 mg Herbal Sedamin capsules containing dried roots of Valeriana Officinallis were consumed by the nurses in the intervention group twice a day for one week. The control group received placebo. The Speilbergerchr('39')s State-Trait anxiety inventory was completed by the nurses at baseline and after the intervention. The independent t-test and paired t-test were used to analyse data. Results: After the intervention in two groups (Valerian and Placebo), the trait and state anxiety scores were significantly lower than before of the intervention. But there were no significant differences in the trait and state anxiety scores of the questionnaire between the experimental group and control groups after the intervention (P=0.846). Conclusion: It seems that the special and different nature of the ICUs has hampered the effectiveness of this herbal medicine. Further studies with higher doses, or in other settings is suggested.